A temperature change in elastic and acoustic properties of auricupride; IOP Conference Series: Materials Science and Engineering; Vol. 124 : Mechanical Engineering, Automation and Control Systems (MEACS2015) - Tesleva E. P. Elena Pavlovna (Materials Science in Mechanical Engineering, 2016)
Title screen